Survival impact and safety of intrathoracic and abdominopelvic cytoreductive surgery in advanced ovarian cancer: a systematic review and meta-analysis - Wang, Jiaxi; Wang, Xingyu; Yin, Wanjun; Zhang, Shiqian (Frontiers in Oncology, 2024)
Purpose Achieving no residual disease is essential for increasing overall survival (OS) and progression-free survival (PFS) in ovarian cancer patients. However, the survival benefit of achieving no residual disease during both intrathoracic and abdominopelvic cytoreductive surgery is still unclear. This meta-analysis aimed to assess the survival benefit and safety of intrathoracic and abdominopelvic cytoreductive surgery in advanced ovarian cancer patients. Methods We systematically searched for studies in online databases, including PubMed, Embase, and Web of Science. We used Q statistics and I-squared statistics to evaluate heterogeneity, sensitivity analysis to test the origin of heterogeneity, and Egger’s and Begg’s tests to evaluate publication bias. Results We included 4 retrospective cohort studies, including 490 patients, for analysis; these studies were assessed as high-quality studies. The combined hazard ratio (HR) with 95% confidence interval (CI) for OS was 1.92 (95% CI 1.38-2.68), while the combined HR for PFS was 1.91 (95% CI 1.47-2.49). Only 19 patients in the four studies reported major complications, and 4 of these complications were surgery related. Conclusion The maximal extent of cytoreduction in the intrathoracic and abdominopelvic tract improves survival outcomes, including OS and PFS, in advanced ovarian cancer patients with acceptable complications. Systematic Review Registration PROSPERO, identifier CRD42023468096